2024
DOI: 10.1002/chem.202303548
|View full text |Cite
|
Sign up to set email alerts
|

Biological Evaluation of Isosteric Applicability of 1,3‐Substituted Cuneanes as m‐Substituted Benzenes Enabled by Selective Isomerization of 1,4‐Substituted Cubanes

Kan Fujiwara,
Shota Nagasawa,
Ryusei Maeyama
et al.

Abstract: We herein evaluate a biological applicability of 1,3‐substituted cuneanes as an isostere of m‐substituted benzenes based on its structural similarity. An investigation of a method to obtain 1,3‐substituted cuneanes by selective isomerization of 1,4‐substituted cubanes enables this attempt by giving a key synthetic step to obtain a cuneane analogs of pharmaceuticals having m‐substituted benzene moiety. Biological evaluation of the synthesized analogs and in silico study of the obtained result revealed a potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…While the 1,3-disubstituted cuneanes (1,3-cuneanes) have been described as early as 1970 by Eaton and co-workers [69] their selective synthesis had not been studied until recently [70]. Selected exit vector parameters showed that substituent distance d and scaffold carbon distance r of 1,3-cuneanes closely resemble the distances found at meta-benzene (Figure 26) [70][71][72]. While the substituent angle φ 1 of 1,3-cuneanes is only slightly larger than in metabenzene, the dihedral angle θ is significantly larger and strongly dependent on the specific substituents.…”
Section: 3-disubstituted Cuneanesmentioning
confidence: 95%
See 3 more Smart Citations
“…While the 1,3-disubstituted cuneanes (1,3-cuneanes) have been described as early as 1970 by Eaton and co-workers [69] their selective synthesis had not been studied until recently [70]. Selected exit vector parameters showed that substituent distance d and scaffold carbon distance r of 1,3-cuneanes closely resemble the distances found at meta-benzene (Figure 26) [70][71][72]. While the substituent angle φ 1 of 1,3-cuneanes is only slightly larger than in metabenzene, the dihedral angle θ is significantly larger and strongly dependent on the specific substituents.…”
Section: 3-disubstituted Cuneanesmentioning
confidence: 95%
“… 1,3-Disubstituted cuneanes as isosteres of meta -benzenes: comparison of selected exit vector parameters [ 70 72 ]. a Reported by Lam and co-workers.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, cuneanes, a class of caged polycyclic hydrocarbons, have garnered interest due to their unique skeleton structure, which enables their applications in liquid crystal technology , and as bioisosteres of benzene , in medicinal development. Their rigid skeleton presents new possibilities for modulating the biological properties of medicinal compounds, while their unique topologies have attracted attention in the fields of both fundamental chemistry and molecular design.…”
Section: Introductionmentioning
confidence: 99%